Synthesis and Antimalarial Evaluation of New 1,3,5-tris[(4-(Substituted-aminomethyl)phenyl)methyl]benzene Derivatives: A Novel Alternative Antiparasitic Scaffold - Sandra Albenque-Rubio; Jean Guillon; Anita Cohen; Patrice Agnamey; Solène Savrimoutou; Stéphane Moreau; Jean-Louis Mergny; Luisa Ronga; Ioannis Kanavos; Serge Moukha; Pascale Dozolme; Pascal Sonnet (MDPI AG, 2023)
A series of new 1,3,5-tris[(4-(substituted-aminomethyl)phenyl)methyl]benzene compounds were designed, synthesized, and evaluated in vitro against two parasites (Plasmodium falciparum and Leishmania donovani). The biological results showed antimalarial activity with IC50 values in the sub and μM range. The in vitro cytotoxicity of these new aza polyaromatic derivatives was also evaluated on human HepG2 cells. The 1,3,5-tris[(4-(substituted-aminomethyl)phenyl)methyl]benzene 1m was found as one of the most potent and promising antimalarial candidates with a ratio of cytotoxic to antiprotozoal activities of 83.67 against the P. falciparum CQ-sensitive strain 3D7. In addition, derivative 1r was also identified as the most interesting antimalarial compound with a selectivity index (SI) of 17.28 on the W2 P. falciparum CQ-resistant strain. It was previously described that the telomeres of P. falciparum could be considered as potential targets of these kinds of aza heterocycles; thus, the ability of these new derivatives to stabilize the parasitic telomeric G-quadruplexes was measured through a FRET melting assay.